TLC and HPLC Enantioseparation of Amino Containing Pharmaceutical Using Levofloxacin as Chiral Derivatizing Reagent in Indirect Method - Lal, Manohar; Kaur, Jaspreet (Asian Journal of Chemistry, 2017)
Indirect reversed-phase high-performance liquid chromatographic (RP-HPLC) and normal phase thin layer chromatographic method was developed for the separation of enantiomers of (RS)-atenolol using levofloxacin as chiral derivatizing reagent. The indirect separations of the derivatized analytes were performed on C18 column in HPLC and on normal phase plane TLC plates. The effects of organic modifier, mobile phase composition, pH and temperature on the separation were investigated.